Investigations on Photodegradation and Antibacterial Activity of Mixed Oxide Nanocrystalline Materials - P. P. Shinde, R. J. Sayyad, S. S. Shukla, S. A. Waghmode and S. R. Gadale (Nature Environment and Pollution Technology)
In this study, we synthesized cobalt-doped molybdenum supported on silica (Co/MS) nanocomposites with varying concentrations of cobalt (1, 5, 10, 15, and 20 wt%) using the sol-gel method. We investigated their physico-chemical properties, photocatalytic activity, and antimicrobial efficacy. The synthesized nanocomposites were characterized using a range of techniques, including X-ray powder diffraction (XRD) to determine crystal structure, UV-vis spectroscopy for optical properties, Fourier transform infrared spectroscopy (FT-IR) for functional group analysis, and scanning electron microscopy coupled with energy-dispersive X-ray microanalysis (SEM-EDX) for morphological and elemental composition analysis. The photocatalytic performance of these catalysts was assessed by their ability to degrade organic dyes, specifically methyl orange and methylene blue, under visible light irradiation. Our results demonstrated that the photocatalytic efficiency increased with higher cobalt content, with the 20 wt% Co/MS nanocomposite showing the highest degradation rates. Additionally, we evaluated the antibacterial activity of the nanocomposites against a range of microorganisms, including Gram-positive and Gram-negative bacteria, as well as fungal species. The 20 wt% Co/MS nanocomposite exhibited superior antimicrobial activity compared to the other samples, indicating its potential for applications in environmental remediation and antimicrobial treatments.